PERFORMANCE OF GLUCOMANNAN-ALGINATE COMBINATION AS A pH SENSITIVE EXCIPIENT OF VITAMIN C ENCAPSULATION USING GELATION METHOD - WARDHANI, DYAH HESTI; CAHYONO, HERI; ARYANTI, NITA (International Journal of Applied Pharmaceutics, 2019)
Objective: This research aimed to develop pH-sensitive vitamin C encapsulation using a combination of biodegradable glucomannan and alginate as an excipient. Methods: Gelation of the excipient was developed by dropping the matrix into the CaCl2 solution to obtain beads. Various ratios of glucomannan-alginate (1:0, 1:1, 1:3, 3:1 and 0:1, g/g), vitamin C concentrations (1, 3 and 5% of total excipient) and excipient preparation methods (mixed glucomannan-alginate matrix, glucomannan beads coated with alginate and alginate beads coated with glucomannan) were selected as variables. Entrapment efficiency of encapsulation and the release of vitamin C were determined at pH 1.2 and 6.8 which represent the pH of the stomach and the small intestine liquid, respectively. Results: Encapsulation of 3% vitamin C using 1:1 (g/g) glucomannan-alginate showed the most efficient matrix. This ratio also had lower released of vitamin C in pH 1.2 compared to that in pH 6.8. Coating the glucomannan bead with alginate showed better ability in encapsulating vitamin C. Combination excipient, as well as the addition of the vitamin C, increased the peak absorbance of the functional groups. The surface morphology of the encapsulation bead depended on the preparation method. Conclusion: An equal ratio of glucomannan and alginate (1:1, g/g) which encapsulated 3% vitamin C showed the most efficient encapsulation as well as lower released vitamin C in pH 1.2 compared to that in pH 6.8. Higher efficiency was observed in encapsulating vitamin C using glucomannan which was coated with alginate.